Solution:
Using the equation:
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
Given the table of values of x and y as shown below:
From the table, when x equals zero, we have y to be -1.4.
Substitute these values of x and y into the above equation.
Thus, we have
![\begin{gathered} y=ax^2+bx+c \\ \Rightarrow-1.4=a(0)^2+b(0)+c \\ \therefore c=-1.4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ir2xhhs12lseltyz2qotm8zdsdpo7x5i49.png)
Substitute the obtained value of c into the equation.
This gives
![y=ax^2+bx-1.4\text{ ---- equation 1}](https://img.qammunity.org/2023/formulas/mathematics/college/wq9v9w9wro0sqf9c8hwu6exyhn2dedcp64.png)
Also, when x equals 0.905, we have y to be zero.
thus, we similarly substitute the values of x and y into the equation.
![\begin{gathered} y=ax^2+bx+c \\ \Rightarrow0=a(0.905)^2+b(0.905)+c \\ 0=0.819025a+0.905b+c \\ \text{but c=-1.4} \\ \text{thus, we have} \\ 0=0.819025a+0.905b-1.4 \\ \Rightarrow0.819025a+0.905b=1.4\text{ ----- equation 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u2frttx5vdmhle2v2gi42w1z61awbf0nxv.png)
When x equals 2, y equals 0.6. substitiute the values of x and y into the equation.
![\begin{gathered} y=ax^2+bx+c \\ \Rightarrow0.6=4a+2b+\text{c} \\ \text{where c=-1.4} \\ \text{thus,} \\ 0.6=4a+2b-1.4 \\ \text{add 1.4 to both sides of the equation,} \\ 0.6+1.4=4a+2b-1.4+1.4 \\ \Rightarrow4a+2b=2\text{ } \\ \text{divide through by 2 reduces the equation to be} \\ 2a+b=1\text{ ------ equation 3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tyvkztfm6o3krzgnhisnsx3f35dxg029dq.png)
From equation 3, make b the subject of the equation or formula.
Thus,
![\begin{gathered} 2a+b=1 \\ \Rightarrow b=1-2a\text{ ---- equation 4} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/90onh5qyvsozg4wnpggftquh55myt50dju.png)
substitute equation 4 intp equation 2.
Thus,
![\begin{gathered} 0.819025a+0.905b=1.4 \\ \text{where} \\ b=1-2a \\ \text{thus,} \\ 0.819025a+0.905(1-2a)=1.4 \\ open\text{ parentheses} \\ 0.819025a+0.905-1.81a=1.4 \\ \text{collect like terms} \\ -0.990975a+0.905=1.4 \\ \text{subtract 0.905 from both sides of the equation} \\ -0.990975a+0.905-0.905=1.4-0.905 \\ \Rightarrow-0.990975a=0.495 \\ \text{divide both sides by the coefficient of a} \\ (-0.990975a)/(-0.990975)=(0.495)/(-0.990975) \\ \Rightarrow a=-0.49950 \end{gathered}]()
To solve for b, substitute the obtained value of a into equation 4.
From equation 4,
![\begin{gathered} b=1-2a \\ \text{where} \\ a=-0.49950 \\ \text{thus,} \\ b=1-2(-0.49950) \\ \Rightarrow b=1.999 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u09yr2ckuyczoah0nj9lds8szraz5aunvz.png)
From the obtained values of a, b, and c, equation 1 becomes
![\begin{gathered} y=ax^2+bx-1.4\text{ } \\ \Rightarrow y=-0.49950x^2+1.999x-1.4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fulnsj261zizt1f0iieok3ovw7g6xbp7a0.png)
Hence, the equation of the parabola is
![y=-0.49950x^2+1.999x-1.4](https://img.qammunity.org/2023/formulas/mathematics/college/aiw9f6bb2zu4e97v84kno8wrstrticnefa.png)